1998
DOI: 10.1007/s005200050179
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with povidone-iodine against induction of oral mucositis by radiochemotherapy

Abstract: Oral mucositis is a frequent complication of radiochemotherapy. The origin of radiation-induced mucosal lesions is iatrogenic in nature, although further development of mucositis is essentially influenced by infection. It can be assumed that disinfection measures should decrease the severity of mucositis induced by radiochemotherapy. Therefore, in a prospective randomised study the efficacy of prophylactic oral rinsing with a disinfection agent was investigated. A randomised, prospective comparative trial was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
15

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 22 publications
(20 reference statements)
0
52
0
15
Order By: Relevance
“…An unblinded RCT of 40 H&N cancer patients undergoing chemoradiation reported that rinsing the mouth with povidone-iodine resulted in reduced incidence of OM as compared to rinsing with sterile water (n=20 in each group) [1,68]. Another study, in patients receiving chemoradiation for esophageal cancer, evaluated an oral hygiene regimen consisting of povidone-iodine mouth rinse in combination with toothbrushing with a special brush, irrigation, suctioning, and cleaning of oral mucosal surfaces, all performed by a dentist.…”
Section: Povidone-iodinementioning
confidence: 99%
“…An unblinded RCT of 40 H&N cancer patients undergoing chemoradiation reported that rinsing the mouth with povidone-iodine resulted in reduced incidence of OM as compared to rinsing with sterile water (n=20 in each group) [1,68]. Another study, in patients receiving chemoradiation for esophageal cancer, evaluated an oral hygiene regimen consisting of povidone-iodine mouth rinse in combination with toothbrushing with a special brush, irrigation, suctioning, and cleaning of oral mucosal surfaces, all performed by a dentist.…”
Section: Povidone-iodinementioning
confidence: 99%
“…Similarly, dexpanthenol, 161,162,165,166 a granulation-promoting agent; caustic compounds such as aluminium hydroxide, and milk of magnesia; 88 and mouth-coating agents including kaolinpectin are part of many multiagent mouthrinses, although their efficacy has not yet been demonstrated in single-agent trials.…”
Section: Mouth-coating Agents and Dexpanthenolmentioning
confidence: 99%
“…Therefore, many prophylactic regimens aimed at the prevention of oral infection by using different anti-infective mouth rinses. [19][20][21][22][23][24][25] The anti-infectives used in our study, that is, PVP, chlorhexidine, polyenes, and sage tea, have been examined in previous clinical trials. Some of these trials examined their effectiveness in preventing or alleviating mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…Mouth rinsing with povidone-iodine successfully prevented oral mucositis in patients receiving combined radiochemotherapy for the treatment of head and neck cancer. 25,33 The present study aimed at the changes of the oral microflora following prophylactic treatment with a combination of different anti-infectives. We found that even through the frequent use of several mouth rinses, the longitudinal impact on bacterial and fungal colonisation was negligible.…”
Section: Discussionmentioning
confidence: 99%